Case Report: Stage IIIc primary malignant mixed Müllerian tumor of the fallopian tube: A case of 5-year disease-free survival after cytoreductive surgery combined with peritoneal resection and adjuvant chemotherapy with paclitaxel plus carboplatin - Xiao, Xiaoli; Ma, Ruiqing; Shi, Lianyao; Wang, Cong; Chen, Jie; Lu, Yiyan; Wang, Yufeng; Zhai, Xichao; Fu, Fengxian (Frontiers in Oncology, 2022)
Malignant mixed Müllerian tumor (MMMT) of the fallopian tube is rare and has a poor prognosis. For the patient with fallopian tube MMMT, complete resection of the tumor invading the viscera and the peritoneum is a prerequisite for long-term survival. We report a case of stage IIIc MMMT of the fallopian tube treated by cytoreductive surgery (CRS), peritoneal resection, and adjuvant chemotherapy (paclitaxel plus carboplatin), with 5-year tumor-free survival. Postoperative chemotherapy combining platinum and paclitaxel is the most potent adjuvant therapy.